ADAR1 deletion induces NFκB and interferon signaling dependent liver inflammation and fibrosis. Issue 5 (4th May 2017) - Ben-Shoshan, Shirley Oren; Kagan, Polina; Sultan, Maya; Barabash, Zohar; Dor, Chen; Jacob-Hirsch, Jasmine; Harmelin, Alon; Pappo, Orit; Marcu-Malina, Victoria; Ben-Ari, Ziv; Amariglio, Ninette; Rechavi, Gideon; et al.
ABSTRACT: Adenosine deaminase acting on RNA (ADAR) 1 binds and edits double-stranded (ds) RNA secondary structures found mainly within untranslated regions of many transcripts. In the current research, our aim was to study the role of ADAR1 in liver homeostasis. As previous studies show a conserved immunoregulatory function for ADAR1 in mammalians, we focused on its role in preventing chronic hepatic inflammation and the associated activation of hepatic stellate cells to produce extracellular matrix and promote fibrosis. We show that hepatocytes specific ADAR1 knock out (KO) mice display massive liver damage with multifocal inflammation and fibrogenesis. The bioinformatics analysis of the microarray gene-expression datasets of ADAR1 KO livers reveled a type-I interferons signature and an enrichment for immune response genes compared to control littermate livers. Furthermore, we found that in vitro silencing of ADAR1 expression in HepG2 cells leads to enhanced transcription of NFκB target genes, foremost of the pro-inflammatory cytokines IL6 and IL8. We also discovered immune cell-independent paracrine signaling among ADAR1-depleted HepG2 cells and hepatic stellate cells, leading to the activation of the latter cell type to adopt a profibrogenic phenotype. This paracrine communication dependent mainly on the production and secretion of the cytokine IL6 induced by ADAR1 silencing in hepatocytes. Thus, our findings shed a new light on the vital regulatory role of ADAR1 in hepatic immune homeostasis, chiefly its inhibitory function on the crosstalk between the NFκB and type-I interferons signaling cascades, restraining the development of liver inflammation and fibrosis.